Transcriptomic profile analysis of the left atrium in spontaneously hypertensive rats in the early stage - Fang, Qinghua; Wang, Jing; Wei, Jiangjun; Long, Xianglin; Wang, Yao; He, Jiacheng; Yuan, Xin; Du, Jianlin (Frontiers in Pharmacology, 2022)
Left atrial remodeling, characterized by enlargement and hypertrophy of the left atrium and increased fibrosis, was accompanied by an increased incidence of atrial fibrillation. While before morphological changes at the early stage of hypertension, how overloaded hypertension influences the transcriptomic profile of the left atrium remains unclear. Therefore, RNA-sequencing was performed to define the RNA expressing profiles of left atrium in spontaneously hypertensive rats (SHRs) and normotensive Wistar-Kyoto (WKY) rats as a control group. We also compared the changes in the RNA expression profiles in SHRs treated with an angiotensin receptor blocker (ARB) and angiotensin receptor-neprilysin inhibitor (ARNI) to assess the distinct effects on the left atrium. In total, 1558 differentially expressed genes were found in the left atrium between WKY rats and SHRs. Bioinformatics analysis showed that these mRNAs could regulate upstream pathways in atrial remodeling through atrial fibrosis, inflammation, electrical remodeling, and cardiac metabolism. The regulated transcripts detected in the left atrial tissue in both the ARB-treated and ARNI-treated groups were related to metabolism. In contrast to the ARB-treated rates, the transcripts in ARNI-treated rats were mapped to the cyclic guanosine monophosphate-protein kinase G signaling pathway.